2015
DOI: 10.1038/gim.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of FBN1 truncating and splicing variants in Marfan syndrome patients with aortic events

Abstract: Original research article introduction FBN1 mutations are most commonly associated with Marfan syndrome (MFS), an autosomal dominant connective tissue disorder typically involving the ocular, skeletal, and cardiovascular systems; MFS less frequently involves the skin, integument, lung, muscle, and adipose tissue. Cardiovascular manifestations, which are the major cause of morbidity and early mortality in MFS, include aortic dilatation at the level of the sinus of Valsalva, predisposition for aortic dissection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
63
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 37 publications
(44 reference statements)
13
63
2
Order By: Relevance
“…In addition, a study by Aoyama et al had already demonstrated in 1995 that mutations leading to a very low deposition of the fibrillin-1 protein (HI) were associated with shortened event-free survival and more severe cardiovascular complications 6. Moreover, among patients with Ghent-positive MFS, a higher frequency of HI- FBN1 mutations was found in patients with cardiovascular events (79%) versus patients without an event (48%, p=0.0039), even at a younger age, compared with patients with a DN- FBN1 mutation 5. Finally, we recently confirmed that patients with an HI- FBN1 mutation are at increased risk for hard clinical endpoints, including aortic dissection and death, compared with those with a DN- FBN1 mutation 15.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study by Aoyama et al had already demonstrated in 1995 that mutations leading to a very low deposition of the fibrillin-1 protein (HI) were associated with shortened event-free survival and more severe cardiovascular complications 6. Moreover, among patients with Ghent-positive MFS, a higher frequency of HI- FBN1 mutations was found in patients with cardiovascular events (79%) versus patients without an event (48%, p=0.0039), even at a younger age, compared with patients with a DN- FBN1 mutation 5. Finally, we recently confirmed that patients with an HI- FBN1 mutation are at increased risk for hard clinical endpoints, including aortic dissection and death, compared with those with a DN- FBN1 mutation 15.…”
Section: Discussionmentioning
confidence: 99%
“…Most mutations are considered to act in a dominant negative way exemplified by missense mutations, or through haploinsufficiency due to nonsense-mediated mRNA decay (NMD) mostly caused by splice-site, frameshift, and nonsense mutations. Although some studies suggest higher probabilities of ectopia lentis in patients with cysteine substitutions 27) and aortic events with truncating/splicing variants, 28) further studies are needed to confirm these relationships.…”
Section: Marfan Syndromementioning
confidence: 97%
“…Cysteine-destroying or cysteine-creating mutations are commonly associated with ectopia lentis (Schrijver et al, 1999). Haploinsufficient mutations, on the other hand, more frequently correlate with aortic events at young ages as well as pectus carinatum, dural ectasia, and skin striae (Baudhuin et al, 2015;Franken et al, 2015). Additionally, the vast majority of the mutations in exons 24-32 are linked to either neonatal MFS or other severe marfanoid presentations (Tiecke et al, 2001).…”
Section: In Search For Strong Genotype-phenotype Correlationsmentioning
confidence: 99%